A simple cost effective carbazole–thiobarbituric acid conjugate as a ratiometric fluorescent probe for detection of mercury(ii) ions in aqueous medium. (30th May 2017) - Kala, K.; Vineetha, P. K.; Manoj, N.
Abstract : A multimode ratiometric Hg 2+ selective chemosensor based on a carbazole–thiobarbituric acid conjugate was developed. It responds to the presence of Hg 2+ by colorimetry and by fluorescence. The sensor action is demonstrated in both aqueous homogeneous or microheterogeneous media. Abstract : A multimode ratiometric Hg 2+ selective chemosensor system based on a carbazole–thiobarbituric acid conjugate (CTBA) was developed. Its colorimetric and fluorescence behavior towards Hg 2+ ions in both homogeneous and microheterogeneous media were investigated. A ratiometric mode of response of absorption as well as fluorescence in acetonitrile and 9 : 1 THF/H2 O medium was observed in the presence of Hg 2+ ions. The sensing mechanism involves formation of a 1 : 2 CTBA : Hg 2+ complex by deprotonation of imide protons of the thiobarbituric acid unit. The complex formation can be reversed by using competing ligands such as cysteamine hydrochloride.